A new name for Justicia reticulata Benoist (Acanthaceae) - Kottaimuthu, Ramalingam; Kumar, Johnkennedy John Praveen; Dineshkumar, Panjavarnam; Logeshwari, Maruthan (Phytotaxa, 2021)
Justicieae is the largest tribe in the family Acanthaceae, notable for its amazing morphological diversity with about 2000 species (Kiel et al. 2017). Among the tribe Justicieae, Justicia Linnaeus (1753: 15) is the most speciose genus with about 935 accepted species (POWO 2021, Tong & Deng 2021). Justicia reticulata Benoist (1946: 146) was described based on the gathering of Perrier from Madagascar. But according to Art.53.1 of ICN (Turland et al. 2018), Benoist’s name is an illegitimate later homonym of J. reticulata Vahl (1804: 157) unfortunately till now this was unnoticed. Therefore, a new name is proposed here for the Malagasy species.